2017
DOI: 10.1186/s12868-017-0363-2
|View full text |Cite
|
Sign up to set email alerts
|

Using Kalirin conditional knockout mice to distinguish its role in dopamine receptor mediated behaviors

Abstract: BackgroundMice lacking Kalirin-7 (Kal7KO), a Rho GDP/GTP exchange factor, self-administer cocaine at a higher rate than wildtype mice, and show an exaggerated locomotor response to experimenter-administered cocaine. Kal7, which localizes to post-synaptic densities at glutamatergic synapses, interacts directly with the GluN2B subunit of the N-methyl-d-aspartate (NMDA; GluN) receptor. Consistent with these observations, Kal7 plays an essential role in NMDA receptor dependent long term potentiation and depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Chronic cocaine induced an increased expression of Kal-7 in the NAc of wild-type mice, and overexpression of Kal-7 in cultured MSNs increased the density of dendritic spine, while knocking out of Kal-7 inhibited the increase in spine density after cocaine treatment, indicating that Kal-7 was supposed to be indispensable for increases of dendritic spine density induced by cocaine (Kiraly et al, 2010;Ma et al, 2012). Lack of Kal-7 did not influence acute locomotor response to cocaine, but it could increase cocaine locomotor sensitization and self-administration (Kiraly et al, 2010(Kiraly et al, , 2013LaRese et al, 2017). After 2 weeks withdrawal from repeated cocaine injections, the levels Kal-7 and the activation of its downstream effectors such as Rac1 and PAK in the NAc were increased, while the surface expression of glutamate receptor AMPAR and spine density also increased (Wang et al, 2013).…”
Section: Rho Gtpases In Cocaine Dependencementioning
confidence: 98%
See 1 more Smart Citation
“…Chronic cocaine induced an increased expression of Kal-7 in the NAc of wild-type mice, and overexpression of Kal-7 in cultured MSNs increased the density of dendritic spine, while knocking out of Kal-7 inhibited the increase in spine density after cocaine treatment, indicating that Kal-7 was supposed to be indispensable for increases of dendritic spine density induced by cocaine (Kiraly et al, 2010;Ma et al, 2012). Lack of Kal-7 did not influence acute locomotor response to cocaine, but it could increase cocaine locomotor sensitization and self-administration (Kiraly et al, 2010(Kiraly et al, , 2013LaRese et al, 2017). After 2 weeks withdrawal from repeated cocaine injections, the levels Kal-7 and the activation of its downstream effectors such as Rac1 and PAK in the NAc were increased, while the surface expression of glutamate receptor AMPAR and spine density also increased (Wang et al, 2013).…”
Section: Rho Gtpases In Cocaine Dependencementioning
confidence: 98%
“…Kal-7 knockdown eliminated the increased expression of AMPAR and spine density, and Kal-7 knockdown rats also exhibited locomotor sensitization, however, incentive sensitization, which was assessed by the speed rats learned to self-administer a threshold dose of cocaine, was impaired severely ( Wang et al, 2013 ). Blockade of NR2B with ifenprodil also inhibited locomotor hypersensitization of cocaine in Kal-7 KO mice ( LaRese et al, 2017 ). These results indicated that Kal-7/Rac1/PAK pathway coordinated glutamate receptors to increase dendritic spine density during cocaine withdrawal, while incentive sensitization and locomotor sensitization may involve divergent mechanisms.…”
Section: Rho Gtpases and Substance Dependencementioning
confidence: 99%
“…Kal7 knockout also resulted in schizophrenia-like effects in adolescent mice (LaRese et al 2017). The Kal7 isoform includes the RacGEF domain but not the RhoGEF domain.…”
Section: Introductionmentioning
confidence: 97%
“…The transcript isoforms can be clustered into two major groups: One group of relatively short isoforms, mostly including the exons at the 5′ end, includes the Kal7 isoform that has been studied extensively in mice and cell culture models. Kal7 knockout also resulted in schizophrenia-like effects in adolescent mice [ 15 ]. The Kal7 isoform includes the RacGEF domain but not the RhoGEF domain.…”
Section: Introductionmentioning
confidence: 99%